2020
DOI: 10.1038/s41416-020-1026-0
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-associated neutrophils orchestrate intratumoural IL-8-driven immune evasion through Jagged2 activation in ovarian cancer

Abstract: Background Tumour associated neutrophils (TANs) play a controversial role in regulating immune surveillance and immune evasion in various malignancies. Here, we investigated the relevance of TANs with the prognosis and immune microenvironment of epithelial ovarian cancer (EOC). Methods We characterised TANs using flow cytometric analysis and immunofluorescence analysis. The prognostic merit of TANs in EOC was evaluated using cox regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 50 publications
3
35
0
Order By: Relevance
“…Tumor cells induce MDSC recruitment in the bladder cancer TME through CXCL2/MIF-CXCR2 signaling, which is correlated with poor prognosis [ 108 ]. CXCL8 contributes to the recruitment of tumor-associated neutrophils that suppress CD8 + T-cell activity, partly depending upon Notch signaling in ovarian cancer [ 109 ]. The expression of CXCR2 is higher in tumor stroma than tumor cells in human lung cancer and correlates with poor prognosis.…”
Section: Cxcl8-cxcr1/2 Signaling Pathwaymentioning
confidence: 99%
“…Tumor cells induce MDSC recruitment in the bladder cancer TME through CXCL2/MIF-CXCR2 signaling, which is correlated with poor prognosis [ 108 ]. CXCL8 contributes to the recruitment of tumor-associated neutrophils that suppress CD8 + T-cell activity, partly depending upon Notch signaling in ovarian cancer [ 109 ]. The expression of CXCR2 is higher in tumor stroma than tumor cells in human lung cancer and correlates with poor prognosis.…”
Section: Cxcl8-cxcr1/2 Signaling Pathwaymentioning
confidence: 99%
“…These mediators primarily consist of chemokines, growth factors, and cytokines. The chemokines CXCL1, 2, 5, 6 and 8, which induce neutrophil chemotaxis through CXCR2/1 chemokine receptors, have been reported to be important for neutrophil recruitment in many cancer types (22,(25)(26)(27)(28)(30)(31)(32)(33)(34)(35)(36)(37)(38). Chemokines are critical to recruit neutrophils not only to primary tumor sites but also to premetastatic niches and metastatic sites.…”
Section: Diffusible Mediators In the Tumor Nichementioning
confidence: 99%
“…Besides mast cells, our previous study also found that tumor-associated neutrophils (TANs), recruited by CXCL8, linked to immune evasion microenvironment and unfavorable survival. 44 Likely, mast cells can release CXCL8 and be recruited and activated by CXCL8. 35 , 45 , 46 Our IHC and flow cytometry results also confirmed the association between sTIMs and TANs.…”
Section: Discussionmentioning
confidence: 99%